The efficacy and safety of Niaoduqing granules in the treatment of diabetic kidney disease: a systematic review and meta-analysis - Chaoqun Song; Zhiyue Zhu; Le Liu; Shilin Liu; Yuandong Li; Yang Xiao; Chunwei Wu; Zheng Nan; Zheng Nan (Frontiers Media S.A., 2023)
Background: Diabetic nephropathy (DN) is the main cause of chronic kidney disease (CKD) and end-stage renal failure (ESRF), and the control of disease progression and adverse events during treatment needs to be improved.Objective: This study aimed to systematically evaluate the clinical efficacy and safety of Niaoduqing granules (NDQG) in the treatment of diabetic kidney disease (DKD).Method: Randomized controlled trials (RCTs) of NDQG for DKD from Chinese and English databases up to 31 August 2022 were included. The quality of the literature was assessed using the risk of bias tool of the Cochrane Handbook. At a 95% confidence interval (CI), relative risk (RR) and Cohen's d were used for the categorical and continuous variables, respectively, and Stata 16.0 software was used for statistical analysis. A funnel plot and Egger's tests were used to assess publication bias.Result: A total of 4,006 patients were included in 52 RCTs, including 1,987 cases in the control group and 2,019 cases in the treatment group. Compared with conventional treatment (CT), combined NDQG therapy is more effective in improving clinical efficiency [RR = 1.23, 95% confidence interval (1.17, 1.29), p < 0.001, I2 = 53.17%], kidney function (urinary albumin excretion rate [SMD = −0.90, 95% CI (−1.14, −0.66), p < 0.001, I2 = 78.19%], 24hUTP levels [SMD = −0.81, 95% CI (−1.08, −0.55), p < 0.001, I2 = 87.08%], blood urea nitrogen [SMD = −0.54, 95% CI (−0.69, −0.39), p < 0.01, I2 = 77.01%], SCr [SMD = −0.68, 95% CI (−0.90, −0.45), p < 0.001, I2 = 89.97%], CCr [SMD = 0.76, 95% CI (0.10,1.42), p = 0.02, I2 = 95.97%], and Cys-C [SMD = −1.32, 95% CI (−2.25, −0.40), p = 0.01, I2 = 93.44%]), the level of glucose metabolism (fasting blood glucose [SMD = −0.18, 95% CI (−0.38, 0.03), p = 0.10, I2 = 71.18%] and HbA1c [SMD = −0.42, 95% CI (−0.86, −0.02), p = 0.06, I2 = 81.64%]), the level of lipid metabolism (total cholesterol [SMD = −0.70, 95% CI (−1.01, −0.39), p < 0.001, I2 = 86.74%] and triglyceride [SMD = −0.61, 95% CI (−0.87,−0.36), p < 0.001, I2 = 80.64%]), inflammatory factors (Hs-CRP [SMD = −1.00, 95% CI (−1.54, −0.46), p < 0.001, I2 = 86.81%], IL-18 [SMD = −1.25, 95% CI (−1.58, −0.92), p < 0.001, I2 = 0], and TNF-α [SMD = −1.28, 95% CI (−1.64, −0.91), p < 0.001, I2 = 75.73%]), and indicators of oxidative stress (malondialdehyde [SMD = −0.88, 95% CI (−1.22, −0.54), p < 0.001, I2 = 66.01%] and advanced oxidation protein products [SMD = −0.92, 95% CI (−1.85, 0.00), p < 0.001, I2 = 90.68%]). In terms of improving uric acid [SMD = −1.59, 95% CI (−3.45, 0.27), p = 0.09, I2 = 94.67%], 2hPG [SMD = −0.04, 95% CI (−0.61, 0.53), p = 0.89, I2 = 84.33%], HDL-C [SMD = 0.71, 95% CI (0.02, 1.40), p = 0.04, I2 = 87.43%], Hb [SMD = 0.11, 95% CI (−0.10, 0.32), p = 0.32, I2 = 0.00]), and superoxide dismutase [SMD = 1.32, 95% CI (0.44, 2.20), p < 0.001, I2 = 93.48%], the effect is not obvious. Adjuvant treatment with NDQG did not increase the incidence of adverse reactions in the control group [SMD = 0.98, 95% CI (0.71, 1.34), p = 0.89, I2 = 1.59%]. Obvious publication bias was detected by funnel plot and Egger's test.Conclusion: Our meta-analysis showed that adjuvant treatment with NDQG has more advantages than conventional treatment alone in the DKD treatment, which could improve clinical efficiency, kidney function, the level of glucose metabolism, the level of lipid metabolism, inflammatory factors, and oxidative stress indicators. At the same time, it also showed that NDQG are relatively safe. However, more high-quality studies are needed to provide more reliable evidence for clinical use.Systematic Review Registration: https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022373726, identifier CRD42022373726.